JURIDICAL ANALYSIS OF THE APPLICATION OF CRIMINAL LAW AND THE SUBSTITUTION OF FINES WITH IMPRISONMENT IN NARCOTICS CASES (STUDY OF DECISION NUMBER 17/PID.SUS/2025/PN/PEMATANGSIANTAR) - Johan Alfred Sarades Silalahi; David L. Manurung; Dwi Nurjanah; Hasty Nadia; Icha A. Napitu; Riz Maharani Tampubolon (RADJA PUBLIKA, 2025)
This study aims to analyze the application of criminal law provisions in Law Number 35 of 2009 concerning Narcotics and the relevance of substituting fines for imprisonment as stated in Decision Number 17/Pid.Sus/2025/PN Pematangsiantar. The problem studied is how the application of criminal law to narcotics crimes in the decision and the extent to which the substitution of fines for imprisonment is in accordance with the principles of justice and the objectives of punishment. The research method used is normative juridical with a statutory approach and case studies of court decisions. The results of the study indicate that the application of criminal law in the decision has been based on the provisions of the Narcotics Law, however, the implementation of substituting fines for imprisonment still raises debate regarding the effectiveness, proportionality, and justice of punishment. In conclusion, although the judge's decision has a clear legal basis, the substitution of fines for imprisonment needs to be reviewed so as not to reduce the essence of the objectives of punishment which are preventive, repressive, and rehabilitative in narcotics cases.